2019
DOI: 10.1016/j.omtn.2019.06.005
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: ANXA3 Silencing Ameliorates Intracranial Aneurysm via Inhibition of the JNK Signaling Pathway

Abstract: Intracranial aneurysm (IA) rupture is a major cause of stroke death. Alteration of vascular smooth muscle cell (VSMC) function and phenotypic modulation plays a role in aneurysm progression. In the present study, we investigated the role of Annexin A3 (ANXA3) silencing in IA with the interaction of the c-Jun N-terminal kinase (JNK) signaling pathway. In IA and VSMCs of IA, the relationship between ANXA3 and the JNK signaling pathway was verified. To investigate the specific mechanism of ANXA3 silencing in IA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…It is notable that, on one hand, improved tumour‐cell survival and proliferation was shown to be mediated, in part, by ANXA3‐mediated caspase 3 (CASP3) suppression 45,50,51 . And in vascular smooth muscle cells a decrease in CASP3 levels was also shown to accompany inhibition of apoptosis and increased proliferation induced by ANXA3 52 . On the other hand, CASP3 is also well‐known to mediate neutrophil programmed cell death: indeed over 1000 records being returned by the PubMed query: neutrophil* AND (‘Caspase 3’ OR CASP3) 53–57 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is notable that, on one hand, improved tumour‐cell survival and proliferation was shown to be mediated, in part, by ANXA3‐mediated caspase 3 (CASP3) suppression 45,50,51 . And in vascular smooth muscle cells a decrease in CASP3 levels was also shown to accompany inhibition of apoptosis and increased proliferation induced by ANXA3 52 . On the other hand, CASP3 is also well‐known to mediate neutrophil programmed cell death: indeed over 1000 records being returned by the PubMed query: neutrophil* AND (‘Caspase 3’ OR CASP3) 53–57 .…”
Section: Resultsmentioning
confidence: 99%
“…45,50,51 And in vascular smooth muscle cells a decrease in CASP3 levels was also shown to accompany inhibition of apoptosis and increased proliferation induced by ANXA3. 52 On the other hand, CASP3 is also well-known to mediate neutrophil programmed cell death: indeed over 1000 records being returned by the PubMed query: neutrophil* AND ('Caspase 3' OR CASP3). [53][54][55][56][57] Specifically, implications in the regulation of The predominance of a given colour in a diagram indicates a tendency of expression of the Annexin family member to be preferentially restricted to a given leucocyte population.…”
Section: Interpretation and Inferences Regarding The Potential Role Of Anxa3 In Sepsismentioning
confidence: 99%
“…Additionally, ANXA3 is a part of the Annexin family and binds to the phospholipids in a Ca 2+dependent manner. It also plays a vital role as a mediator in cellular growth, signal transduction pathways, cancer proliferation, invasion, and migration (Wang et al 2019e). Therefore, LMO7, TSPAN13, LAMA3, and ANXA3 are suggested as the candidates in COPD-IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ANXA3 expression promotes HCC and lung cancer via the JNK signalling pathway (74). Another study reported that ANXA3 silencing ameliorates the intracranial aneurysm by inhibiting the JNK signalling pathway (75). Thus, ANXA3 may exert its role in different types of cancer and diseases via the JNK signalling pathway.…”
Section: Pathways By Which Anxa3 Exerts Its Rolementioning
confidence: 99%